1973
DOI: 10.1126/science.182.4119.1355
|View full text |Cite
|
Sign up to set email alerts
|

Acute Lymphoblastic Leukemic Cells with T (Thymus-Derived) Lymphocyte Markers

Abstract: Five of nine children with acute lymphoblastic leukemia had lymphoblasts that bound sheep erythrocytes or reacted with antiserum to thymocytes, suggesting involvement of T (thymus-derived) cells. When lymphoblasts from all patients were examined by immunofluorescence they were found to lack a marker for B (bone marrow or bursa-equivalent) cells, that is, the presence of surface immunoglobulins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

1974
1974
1980
1980

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(23 citation statements)
references
References 9 publications
2
21
0
Order By: Relevance
“…Ross et al [12] reported that there was not always a good correlation between the presence of surface immunoglobulins and the ability of human leukemic lymphocytes to form EAC rosettes. Interest ingly enough, almost all the cases of acute lymphatic leukemia have been reported to be of T lymphocyte origin [13][14][15], the only exceptions being the case of Gajl Pecjalska et al [16], who had no previous history of chronic lymphatic leukemia, and the two patients described by Brouet et al [3], who supervened on B cell chronic lymphatic leukemia. It is there fore impossible to state whether in our case the small lymphocytes of chronic lymphatic leukemia and the lymphoblasts were derived from the same clone of cells, were two completely unrelated phenomena, or were induced by a common pathogenic factor.…”
Section: Discussionmentioning
confidence: 99%
“…Ross et al [12] reported that there was not always a good correlation between the presence of surface immunoglobulins and the ability of human leukemic lymphocytes to form EAC rosettes. Interest ingly enough, almost all the cases of acute lymphatic leukemia have been reported to be of T lymphocyte origin [13][14][15], the only exceptions being the case of Gajl Pecjalska et al [16], who had no previous history of chronic lymphatic leukemia, and the two patients described by Brouet et al [3], who supervened on B cell chronic lymphatic leukemia. It is there fore impossible to state whether in our case the small lymphocytes of chronic lymphatic leukemia and the lymphoblasts were derived from the same clone of cells, were two completely unrelated phenomena, or were induced by a common pathogenic factor.…”
Section: Discussionmentioning
confidence: 99%
“…Because they react with cells from many, but not all, cases of ALL, they will help to categorize different subtypes of leukemia and may shed light on the tissue origin of these malignant cells. Currently, the human ALLs are subdivided into T cell, pre-B cell, and null cell types according to their expression of certain markers of normal lymphocyte differentiation (27)(28)(29)(30). It is already clear that the antigen defined here is not limited to just the leukemias that carry other T-cell differentiation markers, because it is found on some "null" cell leukemias as well (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…The study of the surface markers of lymphoid cells is of greatest usefulness not only for understanding normal immunity, but also in the analysis of neoplasia affecting the lymphopoietic system [12]. As for pediatric patients only, pathological cells of subjects with acute lymphocytic leukemia (ALL) have been found to possess in general impaired markers either for B or T cells [2,4,8,14,16,18].…”
Section: Discussionmentioning
confidence: 99%